2004
DOI: 10.1016/j.euje.2004.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Localization and quantification of mitral valve prolapse using three-dimensional echocardiography

Abstract: In patients with severe mitral regurgitation due to mitral valve prolapse, 3D echo allowed a precise localization and an accurate quantification of the prolapsing portion of the leaflets. This technique can provide refinements in the surgical planning of mitral valve repair and in the selection of candidates for this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 19 publications
0
32
0
1
Order By: Relevance
“…More recently, software advances have reduced the mean acquisition and reconstruction times increasing the clinical feasibility of the technique. However, despite significant clinical advantages of 3D-TOE over 2D-TOE particularly for the localization of MV prolapse [7,9,10,22,23], 3D-TOE based on the imaging reconstruction has not been universally accepted in routine clinical practice because of its cost and the need for offline processing. The miniaturization of previously developed transthoracic 3D matrix-array transducers has allowed their adaptation into the tips of otherwise conventional transoesophageal probes, resulting in fully sampled matrix-array transducers.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, software advances have reduced the mean acquisition and reconstruction times increasing the clinical feasibility of the technique. However, despite significant clinical advantages of 3D-TOE over 2D-TOE particularly for the localization of MV prolapse [7,9,10,22,23], 3D-TOE based on the imaging reconstruction has not been universally accepted in routine clinical practice because of its cost and the need for offline processing. The miniaturization of previously developed transthoracic 3D matrix-array transducers has allowed their adaptation into the tips of otherwise conventional transoesophageal probes, resulting in fully sampled matrix-array transducers.…”
Section: Discussionmentioning
confidence: 97%
“…However, the severity and magnitude of prolapse has been difficult to accurately determine preoperatively using 2D TEE, especially in valves with multisegmental lesions. 20,21 This is probably the case because 3D TEE is less operator-dependent than 2D TEE that relies on fine adjustments of the TEE probe and mental integration of a limited number of 2D imaging planes to delineate MV pathology. Analysis in a subset of our patients demonstrated higher agreement between qualitative assessment of 3D images and surgical findings when compared with 2D images.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) TEE has been demonstrated to be superior to bi-dimensional (2D) imaging in the description of all different forms of mitral valve pathology, and particularly helpful in complex valve disease with the involvement of several scallops and of commissural segments with high negative predictive value [3][4][5][6]. Additionally, first studies with International Journal of Cardiology 127 (2008) 342 -349 www.elsevier.com/locate/ijcard transthoracic real-time 3D echocardiography (RT3DE) have been performed and demonstrated that RT3DE of mitral valve is feasible in a large majority of patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%